1996
DOI: 10.1200/jco.1996.14.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant cyclophosphamide, methotrexate, and fluorouracil versus fluorouracil, epirubicin, and cyclophosphamide chemotherapy in premenopausal women with axillary node-positive operable breast cancer: results of a randomized trial. The International Collaborative Cancer Group.

Abstract: We conclude that the FEC2 regimen, in which epirubicin replaced the methotrexate in CMF, is the preferable adjuvant chemotherapy regimen for premenopausal patients with operable axillary node-positive breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(43 citation statements)
references
References 18 publications
2
39
0
2
Order By: Relevance
“…The FASG-01 conducted in premenopausal, node-positive breast cancer patients showed that six cycles of FEC 50 were significantly better than three cycles of FEC 50 or FEC 75 in terms of 10-year DFS (14). The FEC regimen remains widely accepted in Europe, while four cycles of the AC regimen (doxorubicin and cyclophosphamide) is commonly used in the USA, based on the NSABP B-15 trial which showed results similar to those obtained using six cycles of CMF (cyclophosphamide, methotrexate, and fluorouracil) (15). AC was preferable since, following total mastectomy, AC was completed on day 63 versus day 154 for conventional CMF; patients visited health professionals three times as often for conventional CMF as for AC; and nausea-control medication was given for about 84 days to conventional CMF patients versus for about 12 days to patients on AC.…”
Section: Role Of Anthracyclinessupporting
confidence: 49%
“…The FASG-01 conducted in premenopausal, node-positive breast cancer patients showed that six cycles of FEC 50 were significantly better than three cycles of FEC 50 or FEC 75 in terms of 10-year DFS (14). The FEC regimen remains widely accepted in Europe, while four cycles of the AC regimen (doxorubicin and cyclophosphamide) is commonly used in the USA, based on the NSABP B-15 trial which showed results similar to those obtained using six cycles of CMF (cyclophosphamide, methotrexate, and fluorouracil) (15). AC was preferable since, following total mastectomy, AC was completed on day 63 versus day 154 for conventional CMF; patients visited health professionals three times as often for conventional CMF as for AC; and nausea-control medication was given for about 84 days to conventional CMF patients versus for about 12 days to patients on AC.…”
Section: Role Of Anthracyclinessupporting
confidence: 49%
“…CMF reported by Coombes et al, 30 one case of nonfatal cardiomyopathy thought to be related to FEC was observed. The study by Martin et al 35 reported a 1.5% incidence of grade 1-2 cardiac toxicity and a 0.6% incidence of grade 3-4 cardiac toxicity after FAC, compared with a 0.2% incidence of grade 1-2 cardiac toxicity after i.v.…”
Section: Cardiotoxicitymentioning
confidence: 98%
“…CMF. 25,28,[30][31][32]35,46 The NSABP B-15 trial also showed that the AC (doxorubicin and cyclophosphamide) regimen was associated with more prolonged and, in some cases, intractable, vomiting than either oral or i.v. CMF 25 but that oral CMF was associated with greater nausea than either i.v.…”
Section: Acute Toxicitiesmentioning
confidence: 99%
See 2 more Smart Citations